2017
DOI: 10.1038/s41550-017-0152
|View full text |Cite
|
Sign up to set email alerts
|

A rotating protostellar jet launched from the innermost disk of HH 212

Abstract: The central problem in forming a star is the angular momentum in the circumstellar disk which prevents material from falling into the central stellar core. An attractive solution to the "angular momentum problem" appears to be the ubiquitous (low-velocity and poorlycollimated) molecular outflows and (high-velocity and highly-collimated) protostellar jets accompanying the earliest phase of star formation that remove angular momentum at a range of disk radii 1 . Previous observations suggested that outflowing ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
107
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 132 publications
(115 citation statements)
references
References 32 publications
(71 reference statements)
5
107
0
Order By: Relevance
“…A DW model fit, with λ = 5.5 and W = 30 (see text), is overplotted in black for parameters denoted in each panel. Panels e−f : PV diagrams observed by Lee et al (2017a) across the SiO knots N2 and S3 (grayscale and black/red contours). Their measured centroids are shown as green squares and fitted rotation gradient as a black line.…”
Section: Comparison With Mhd Disk Wind Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…A DW model fit, with λ = 5.5 and W = 30 (see text), is overplotted in black for parameters denoted in each panel. Panels e−f : PV diagrams observed by Lee et al (2017a) across the SiO knots N2 and S3 (grayscale and black/red contours). Their measured centroids are shown as green squares and fitted rotation gradient as a black line.…”
Section: Comparison With Mhd Disk Wind Modelsmentioning
confidence: 99%
“…The SO 2 (8 2,6 −7 1,7 ) line at 334.67335 GHz was observed with a spectral resolution of 1 km s Lee et al (2017a); the yellow ellipse marks the centrifugal barrier radius at r ∼ 45 au and the height of the COM-rich disk atmosphere at z ± 20 au (Lee et al 2017c). Images are rotated such that the vertical axis corresponds to the jet axis at PA = 22…”
Section: Observationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Detailed models are successful at reproducing the higher molecule richness of Class 0 jets (Panoglou et al 2012) the broad water line components revealed by Herschel/HIFI (Yvart et al 2016), and the rotation signatures recently resolved by ALMA in the HH212 jet and in the slow wider angle wind surrounding it (Lee et al 2017;Tabone et al 2017). However, the same disk wind models predict that the fastest, SiO-rich streamlines in HH212 (flowing at ∼ 100 km s −1 ) would be launched from 0.05-0.2 au, within the dust sublimation radius (Tabone et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Yet, jets from the youngest protostars -so-called Class 0 -are much brighter in molecules (e.g., Tafalla et al 2000) than jets from more evolved protostars and pre-main sequence stars which are mainly atomic; Molecules have been traced as close as 20-100 au from the source (e.g., Lee et al 2017;Hodapp & Chini 2014). The origin of this selective molecular richness remains an important issue for models of the jet origin.…”
Section: Introductionmentioning
confidence: 99%